The National Museum of Mongolia successful strategies and lessons learned (Cadernos de Sociomuseologia, 2012)
Enkhnaran will discuss issues for professional education raised by museums and tourism companies, which share similar objectives in the sense that each aim to provide their guests with quality information entertainment and a memorable experience. With limited budget capabilities, it is especially important for museums to co-operate with tourist companies in order to attract new and repeat visitors as well as generate important revenue.